The DEHVILS survey overview and initial data release: high-quality near-infrared Type Ia supernova light curves at low redshift. Issue 2 (13th April 2023) - Peterson, Erik R; Jones, David O; Scolnic, Daniel; Sánchez, Bruno O; Do, Aaron; Riess, Adam G; Ward, Sam M; Dwomoh, Arianna; de Jaeger, Thomas; Jha, Saurabh W; Mandel, Kaisey S; Pierel, Justin D R; et al.
ABSTRACT: While the sample of optical Type Ia supernova (SN Ia) light curves (LCs) usable for cosmological parameter measurements surpasses 2000, the sample of published, cosmologically viable near-infrared (NIR) SN Ia LCs, which have been shown to be good 'standard candles, ' is still ≲ 200. Here, we present high-quality NIR LCs for 83 SNe Ia ranging from 0.002 < z < 0.09 as a part of the Dark Energy, H0, and peculiar Velocities using Infrared Light from Supernovae (DEHVILS) survey. Observations are taken using UKIRT's WFCAM, where the median depth of the images is 20.7, 20.1, and 19.3 mag (Vega) for Y, J, and H -bands, respectively. The median number of epochs per SN Ia is 18 for all three bands ( Y, J, and H ) combined and 6 for each band individually. We fit 47 SN Ia LCs that pass strict quality cuts using three LC models, SALT3, snoopy, and B aye SN and find scatter on the Hubble diagram to be comparable to or better than scatter from optical-only fits in the literature. Fitting NIR-only LCs, we obtain standard deviations ranging from 0.128 to 0.135 mag. Additionally, we present a refined calibration method for transforming 2MASS magnitudes to WFCAM magnitudes using HST CALSPEC stars that results in a 0.03 mag shift in the WFCAM Y -band magnitudes.